n-FOLD INCREMENTATION OF LINGUISTIC VARIABLES ORDER METHOD, BASED ON PARTICULAR BASE EXPANSION - Корченко, Александр Григорьевич; Ахметов, Бахытжан Сражатдинович; Казмирчук, Светлана Владимировна; Жекамбаева, Майгуль Несипалдиевна (Ukrainian Information Security Research Journal, 2015)
Existing risk analysis and assessment systems are basedon linguistic variables processing, which in turn, are basedon etalon parametric trapezoidal fuzzy numbers with adifferent number of defining terms, the formation ofwhich is related to the involvement of experts in therelevant subject area. Practical use efficiency of this kindof systems depends on its ability to process different typeof fuzzy numbers and on the vary efficiency of number ofterms without the involvement of appropriate experts. Nfoldincrementation of linguistic variables order method,based on the second particular base expansion, that wouldallow to formalize the process of the equal transformationof the number of terms of linguistic variable in n-orders isbeing proposed to solve this problem. This will help toimprove the appropriate information security risk analysisand assessment system, at the expense of etaloncorrection procedure simplification, by implementing theprocess of the n-fold incrementation of number of termsfor trapezoidal fuzzy numbers.